THE TRANSFORMATION OF COMMUNICATION TECHNOLOGY AND ITS INFLUENCE ON MODERN SOCIETY’S LIFESTYLE PATTERNS - Daulay, Nadhira Anggraini; Nasution, Muhammad Irwan Fadli; Sundari, Sri Suci Ayu (MediaKom : Jurnal Ilmiah Komunikasi, 2025)
The transformation of communication technology has brought fundamental changes to the lives of modern society, especially in the way individuals interact, access information, and form patterns of daily social behavior. This study aims to analyze the impact of changes in communication technology on the lifestyle of modern society, with a focus on the intensity of digital media use, changes in interpersonal communication patterns, and their influence on lifestyle and social culture. The method used in this study is a descriptive qualitative approach with data collection techniques through in-depth interviews, participatory observation, and literature studies of urban communities that actively use digital communication technology. The results of the study indicate that the transformation of communication technology, especially through social media and instant messaging applications, has created a more dynamic lifestyle but is also vulnerable to disruption of traditional social values. Modern society tends to form a digital identity, experience a shift in the way they socialize, and become dependent on gadgets in carrying out daily activities, including working, studying, and interacting socially. This study also found that although communication technology increases efficiency and connectivity, it also poses new challenges such as decreased face-to-face interaction, increased individualism, and the potential for social isolation. Therefore, an adaptive strategy is needed in the use of technology that is oriented towards a balance between digital progress and strengthening social values. This study makes an important contribution to understanding the relationship between communication technology and social change in the context of a modern society that continues to develop dynamically.